Facility Management - Rastogi, S. A.; Bhalerao, J. V. (Indian Journal of Marketing, 2008)
The term 'Facility Management' is generally preferred in United States usage, while 'facilities management' is more common in UK, Canada, Australia and English-medium businesses in several European countries.In India Facility Management is of a recent origin and is growing at 50% CAGR as businesses have identified the need and benefits of specialized Facility Management service providers. The reason being the companies can focus on their core businesses by outsourcing non-core support activities like Facility Management.